Everolimus inhibits glomerular endothelial cell proliferation and VEGF, but not long-term recovery in experimental thrombotic microangiopathy - Keller, Katja; Daniel, Christoph; Schöcklmann, Harald; Endlich, Karlhans; Kerjaschki, Dontscho; Johnson, Richard J.; Hugo, Christian (Nephrology Dialysis Transplantation, 2006)
Background. Everolimus is a potent immunosupressant used in renal transplant therapy, but its effects on renal endothelial cell regeneration after injury are unknown. The effects of an everolimus therapy were investigated in a model of renal thrombotic microangiopathy (TMA) with specific endothelial cell (EC) injury in the rat in vivo as well as in glomerular ECs in vitro. Methods. During the early regenerative phase (day 3) of the renal microvascular injury model in vivo, everolimus inhibited glomerular EC proliferation by up to 60% compared with vehicle-treated rats, whereas apoptosis was not different in these groups. This decreased EC proliferation was associated with an enhanced deposition of fibrin in everolimus treated animals on day 3. In cultured glomerular endothelial cells, everolimus effectively and dose dependently inhibited cellular proliferation. This anti-proliferative effect was associated with a reduced phosphorylation of the p70S6 kinase and reduction of the pro-angiogenic factor VEGF in glomeruli in vivo and in cultured podocytes in vitro. Results. Despite the prolonged EC repair and in contrast to the anti-Thy1 nephritis model, everolimus therapy did not disturb the long-term repair reaction in this thrombotic microangiopathy model. Conclusion. Everolimus is anti-proliferative for glomerular EC in vitro and in vivo and does not seem to have detrimental long-term effects in experimental renal TMA, when only the glomerular endothelium, but not the mesangium is severely injured. © 2006 Oxford University Press.
Created from Fastlane, Scopus look-up
Keywords: Glomerular endothelial cell proliferation; Glomerulosclerosis microvascular injury; Rapamycin derivative everolimus; VEGF